"He's My Dad Because He Just Is!": Cohabiting (Step)Children's Responses to Discursive Challenges. Issue 4 (19th May 2017) - Nuru, Audra K.; Wang, Tiffany R.
ABSTRACT: Cohabiting (step)families have become one of the fastest growing family forms in the United States. This study explored the types of discursive challenges experienced by cohabiting (step)children, as well as the ways in which cohabiting (step)children might respond to potential challenges of legitimacy. In this study, we interviewed 28 (step)children who resided with 1 biological parent and their parent's nonmarital partner for at least 2 years. Results demonstrate that despite recent increases in prevalence and acceptance of unmarried partner households, cohabiting (step)children are often called on to explain their family's legitimacy through accounting strategies when they experience discursive challenges to their (step)family's form.